Study on patient satisfaction among patients with trauma admitted to trauma centre and emergency medical services ward - Uppin, Mrutyunjay I.; Hannurkar, Kapildev K.; Uppin, Archana M. (International Surgery Journal, 2019)
Background: Patient satisfaction is an important key factor for determining the quality health care and services offered by the emergency departments in the hospital. The objectives of the study were to assess the satisfaction of the trauma patients attending the trauma center with the services provided by the KLES Dr. Prabhakar Kore Hospital and Research Centre, Belagavi, Karnataka. Methods: Fifty trauma patients admitted and treated in trauma center and emergency medical services ward (TCEMS) at KLES Dr. Prabhakar Kore Hospital and Research Centre, Belagavi, over a period of 3 months (from November 2014 till January 2015) were interviewed. After obtaining an informed consent, the required data was collected using a pre-designed and pre-tested questionnaire. Results: Out of the 50 patients interviewed, 86% were males and 14% were females. Out of them 74% were road traffic accident victims. 67.5% of these victims were between the age group of 21 and 50 yrs. The overall satisfaction was good with all the services provided at the center. 80% were satisfied with the care provided by the doctors, 80% with communication by doctors, more than 75% with accessory services, more than 65% with the wait times at various levels and more than 85% satisfaction with amenities in the ward. Conclusions: In conclusion our study revealed that the availability of consultant in triage area, improvements in communication, quick service at the Casualty Pharmacy, reducing the perceived waiting times at various levels and improvement in the ambience of the unit would further enhance the patient satisfaction with TCEMS.